Creating Growth by Connecting PlaceBased Development Strategies - Mariussen, Åge; Hegyi, Fatime Barbara (Publications Office of the European Union, 2020)
In the past years, the European Commission launched three thematic Smart Specialisation platforms to support interregional collaborations and to support European Union regions committed to co-invest jointly in strategic growth areas. The bottom up component in this process has resulted in a wide variety of industry-scientific partnerships at regional and transnational levels. These networks include regions, which are very different in terms of innovation ecosystems, but nevertheless connected through shared thematic focus enabling transnational processes of innovation. This paper explains how interregional partnerships build on the efforts and results achieved in national and regional research and innovation strategies for Smart Specialisation and how, as a result of this, new European innovation ecosystems are emerging. With reference to existing literature and experiences so far, the paper outlines a conceptual framework of how transnational cooperation may strengthen regional place-based development strategies and improve regional innovation capabilities. Key analytical concepts are proximity, knowledge complexity, entrepreneurial discovery processes, stakeholder analysis and cluster emergence.
Keywords: business cluster; economic growth; entrepreneurship; industry-research relations; innovation; international cooperation; regional cooperation; regional development; research and development; research report; fi=Aluetiede|en=Regional Studies|